Temptation in the background: non-consummatory exposure to food temptation enhances self-regulation in boys but not in girls - Grubliauskiene, Aiste; Dewitte, Siegfried (Frontiers in Psychology, 2014)
The abundance of calorie-dense low-nutrient food in everyday life raises the question as to how children deal with such opportunities. We investigate whether pre-exposure to the object of temptation in a situation that discourages consumption boosts children’s ability to resist similar temptation subsequently. We show that 7–12-year-old boys, but not girls, demonstrate increased resistance to a temptation after pre-exposure to a similar temptation. Future research might explore the role of exposure to temptation in girls.